Faktor-Faktor yang Mempengaruhi Keputusan Mahasiswa Membeli Makanan Berprotein Hewani - Roisu Eny Mudawaroch (Universitas Muhammadiyah Purworejo, 2020)
Students have a strong personality so that they can make choices, one of which is the purchase of the food they consume. The purpose of this study was to determine 1) the influence of social factors on purchasing decisions for animal protein food; 2) Personal factors in animal protein food purchasing decisions; 3) Knowledge factors about animal protein food purchasing decisions and 4) Social factors, personal factors and knowledge factors about animal protein food purchasing decisions. The sample used was 90 students. The data obtained in the classical assumption test include normality test, validity test, reliability test, multicollinearity test, and heteroscedasticity test. The data were analyzed multiple linear regression with social factors (X1) personal factors (X2), knowledge factors (X3), while the decision to buy animal protein foods (Y). The results of the classical assumption test show the Kolmogorov-Smirnov normality test which shows the data was normally distributed. The results of the validity test of all instruments were valid. Reliability test results show the instrument used was reliable. The multicollinearity test results showed that there was no multicollinearity. The results of the heteroscedasticity test did not show any heteroscedasticity. The results of linear regression analysis showed Y = 4.574-0.105 (X1) +0.121 (X2) +0.004 (X3). The results of the F test showed a significant effect. And from the results of the determination test, the value of R = 0.313 was obtained. The conclusion was that social factors have an effect on animal protein food purchasing decisions, personal factors do not affect the animal protein food purchase decisions, knowledge factors do not affect animal protein food purchasing decisions, social factors, personal factors and knowledge factors jointly influence purchasing decisions. protein food animal.